Relation between macroscopic binding constant and the anticancer efficacy of the bovine serum albumin-quercetin complex against drug-sensitive and drug-resistant cells - Choiprasert W. (2014)
Problem statement: We have previously analyzed the interaction of BSA with flavonoidsby using FRET. In this study, the role of BSA on increasing in solubility and on carrying the quercetinderivatives thus enhanced their anticancer efficacy against drug-sensitive and drug-resistant cells wereconducted. Approach: The macroscopic (KD) and microscopic (Kd) binding constant of thecomplexation and the cellular partition of molecules were analyzed using FRET and HPLC method,respectively. Results: The KD values reflex the stability of complexes was in the order of rutin >quercetrin > quercetin. BSA was a suitable carrier of quercetin (KD = 1.68×105M-1) which spontaneously release the molecule into solutions and cells. The substitution of rhamnoside (KD =1.37×105 M-1) and rutinoside (KD = 5.0×104M-1) at C3 yielded an increase in stability of thecomplexes. Rutin was tightly bound to BSA resulting in the changes in mode of action. Conclusion:The macroscopic binding constant was directly influenced on the cellular uptake of molecules and thesuitable range of binding constant was KD≥105M-1 by which the carrier can be useful for increasingthe solubility of drug and also spontaneously release the drug into the solution and cells. © 2010 Science Publications.